Recent student mobilizations and their contributions to educational purposes - Pavani , Marcos Roberto (Seven Editora, 2024)
This text was developed based on the research, readings and discussions carried out in the author’s doctoral course, in the Graduate Program in Education of the Federal University of São Carlos (UFSCar), especially in the debates that took place at the Center for Studies and Research of the Vygotsky School (NEEVY), between the years 2017 and 2021 and in the discipline Critical Theory and Education of the aforementioned program, as well as through documentary research on the topic addressed. The concepts discussed here are based on Critical Theories and Historical-Cultural Theory and are part of the analyses presented in the resulting thesis, defended by the author in 2021. It carries out an analysis of the student mobilizations that have recently taken place in Brazil, drawing a comparison with other Brazilian historical contexts, in order to promote a discussion about the causes of the current struggles, their coping mechanisms and some of the main educational results obtained. DOI:https://doi.org/10.56238/sevened2024.010-066